Analysis of the Effect of Debt to Profit on PT Bukit Uluwatu Villa, Tbk - I G A Mas Yunita Sari; I D M Mahayana; I G M Karma (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
The main purpose of a company is to get optimal profit, if the company's profit decreases, the company must increase its business capital so that the company can continue to operate. Generally, because of the need for funds is too high, the company decides to increase capital from external sources such as debt. The purpose of this study is to determine whether there is an influence of short-term debt and long-term debt on the company's operating profit. The type of data used was a quantitative data type in the form of a statement of financial position and income statement from 2010 to 2018. The data source was a secondary data source from idx.co.id, and the data were collected using documentation method. The analysis technique applied was a quantitative analysis technique in the form of multiple linear regression analysis. This study found that partially and simultaneously short-term debt and long-term debt had no significant effect on operating profit of PT Bukit Uluwatu Villa, Tbk.